Atmospheric polygeneration with hydrogen storage - Nurettin Sezer (14778217) (2024)
This study presents the design and analysis of an atmospheric polygeneration system, which integrates solar photovoltaics, Vapor Compression Refrigeration Cycle (VCRC), electrodeionization, water electrolysis, hydrogen storage and fuel cell. The system is designed for autonomous and continuous operation to provide electricity, water, space cooling, and hydrogen using only natural sunlight and humid air as renewable resources. Thermodynamic analysis is carried out for the entire system including each subsystem and auxiliaries. Psychrometric calculations are conducted for atmospheric water harvesting and cooling generation. The electrochemistry and inherent overpotentials of the electrolysis cell and fuel cell are elucidated. Further, a parametric study is conducted to analyze the impact of varying parameters on the efficiency, performance, and output rates of the system. According to the results, the proposed system generates 5 kW electricity, 8.2 tons cooling, 28.36 L/h atmospheric water, and 17 kg hydrogen during daytime operation at an energy and exergy efficiency of 10.7% and 7.6%, respectively. The same rate of atmospheric water and cooling is generated during night, consuming a total of 7.3 kg of the daytime produced hydrogen, and the energetic and exergetic coefficient of performance of nighttime operation are identified as 1.58 and 0.28, respectively. Besides, the roundtrip energy and exergy efficiency of the hydrogen system is calculated as 35.8% and 46.1%, respectively. The comprehensive study reported in this article demonstrates the thermodynamic performance of using inexhaustible natural atmospheric resources for sustainable polygeneration to serve communities in hot and humid climates. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2024.12.290